Borrowing Agreement with Norges Bank. (Policy Papers; Policy Paper ;, 2009)
This paper presents for the approval of the Executive Board a draft borrowing agreement between Norges Bank and the Fund. On March 28, the Finance Minister of Norway announced that the Ministry of Finance and Norges Bank (the central bank of Norway) were exploring a possible Norwegian contribution of up to 30 billion Norwegian kroner (about USD 4.5 billion or SDR 3 billion) of financial resources to the IMF to support the Fund's ability to provide timely and effective balance of payments assistance to its members in the current crisis. Staff and Norges Bank representatives have now reached agreement on a draft borrowing agreement, the text of which is set forth in the Attachment ('the Agreement').